Myelofibrosis: Treatment Options After Ruxolitinib Failure - Ruth Stuckey; Adrián Segura Díaz; María Teresa Gómez-Casares (Current Oncology, 2025)
While allogeneic hematopoietic stem cell transplantation remains the only curative therapy for patients with myelofibrosis, its applicability is limited both by the high morbidity and mortality associated with the procedure and by the fact that only a minority of patients are eligible due to age or comorbidities. Ruxolitinib, a JAK1/JAK2 inhibitor, is the standard first-line therapy for intermediate- and high-risk MF, offering symptom relief and splenic volume reduction but lacking a clear survival benefit. Its use may be limited by hematologic toxicities, increased infection risk, and an inability to prevent disease progression. Ruxolitinib failure remains a significant clinical challenge, with resistance mechanisms not fully elucidated. The approval of other JAK inhibitors—fedratinib, pacritinib, and momelotinib—has expanded treatment options, particularly for patients with cytopenias or transfusion dependence. Moreover, many other targeted agents are in development in clinical trials, as monotherapy or in combination with ruxolitinib. This review provides an update on the use of JAK inhibitors and novel agents, with a focus on treatment options for ruxolitinib-resistant or refractory patients. As therapeutic strategies evolve, optimizing treatment sequencing and incorporating next-generation sequencing will be critical for improving patient outcomes.